Non‐psychotropic Cannabis sativa L. phytocomplex modulates microglial inflammatory response through CB2 receptors‐, endocannabinoids‐, and NF‐κB‐mediated signaling. (8th April 2022) - Borgonetti, Vittoria; Benatti, Cristina; Governa, Paolo; Isoldi, Giovanni; Pellati, Federica; Alboni, Silvia; Tascedda, Fabio; Montopoli, Monica; Galeotti, Nicoletta; Manetti, Fabrizio; Miraldi, Elisabetta; Biagi, Marco; et al.
Abstract: Cannabis sativa L. is increasingly emerging for its protective role in modulating neuroinflammation, a complex process orchestrated among others by microglia, the resident immune cells of the central nervous system. Phytocannabinoids, especially cannabidiol (CBD), terpenes, and other constituents trigger several upstream and downstream microglial intracellular pathways. Here, we investigated the molecular mechanisms of a CBD‐ and terpenes‐enriched C . sativa extract (CSE) in an in vitro model of neuroinflammation. We evaluated the effect of CSE on the inflammatory response induced by exposure to lipopolysaccharide (LPS) in BV‐2 microglial cells, compared with CBD and β‐caryophyllene (CAR), CB2 receptors (CB2r) inverse and full agonist, respectively. The LPS‐induced upregulation of the pro‐inflammatory cytokines IL‐1β, IL‐6, and TNF‐α was significantly attenuated by CSE and only partially by CBD, whereas CAR was ineffective. In BV‐2 cells, these anti‐inflammatory effects exerted by CSE phytocomplex were only partially dependent on CB2r modulation and they were mediated by the regulation of enzymes responsible for the endocannabinoids metabolism, by the inhibition of reactive oxygen species release and the modulation of JNK/p38 cascade with consequent NF‐κB p65 nuclear translocation suppression. Our data suggest that C . sativa phytocomplex and its multitarget mechanism could represent a novel therapeutic strategy for neuroinflammatory‐related diseases.